2013
DOI: 10.1074/jbc.m112.434357
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Type VI Effector-Immunity Complex (Tae4-Tai4) Provides Novel Insights into the Inhibition Mechanism of the Effector by Its Immunity Protein*

Abstract: Background:The bacteria effector Tae4 is injected into the recipient cells to kill them and the immunity protein Tai4 is produced to inactivate Tae4. Results: Tae4 displays a papain-like fold, and Tai4 dimer is responsible for inhibiting Tae4 activity. Conclusion:The inactivation of Tae4 is required by collaboration of both subunits of Tai4 dimer. Significance: Our results add new insights into the effector-immunity interaction module.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
79
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 38 publications
11
79
0
Order By: Relevance
“…For example, we found that E. cloacae is not killed by the SPI-6 attack. This result is in agreement with the fact that the genome of E. cloacae encodes a Tai4 immunity protein that has been shown to bind and inhibit S. Typhimurium Tae4 activity (35,57). In our study, we found that the ability of S. Typhimurium to kill E. coli was strain-dependent.…”
Section: Discussionsupporting
confidence: 80%
“…For example, we found that E. cloacae is not killed by the SPI-6 attack. This result is in agreement with the fact that the genome of E. cloacae encodes a Tai4 immunity protein that has been shown to bind and inhibit S. Typhimurium Tae4 activity (35,57). In our study, we found that the ability of S. Typhimurium to kill E. coli was strain-dependent.…”
Section: Discussionsupporting
confidence: 80%
“…Given the two oligomeric forms of VgrG-3C/TsaB as observed through size exclusion chromatography using the same preincubation conditions, we hypothesize that the incomplete inhibition of PGdegrading activity may arise from unsaturation of VgrG-3C. Zhang et al (19) describe a similar interaction between Tae4 and Tai4, a toxin-antitoxin pair of the Enterobacter cloacae T6SS, in which an antitoxin dimer is required to inactivate the Tae4 toxin. These results indicate that TsaB has a direct inhibitory effect on the lytic activity of VgrG-3C.…”
Section: Delivery Of Vgrg-3 or Vgrg-3c To The Periplasm Is Toxic To Ementioning
confidence: 98%
“…1A) (41). The gene cluster encodes all the genes required to assemble a functional secretion apparatus, as well as three effectors (STM0277, tae4; STM0291 and STM0292, rhs) and their cognate immunity proteins (STM0278, tai4; STM0291b and STM0293, rhsI) (42)(43)(44)(45). tae4 encodes a toxin with peptidoglycan hydrolase activity, whereas the Rhs C-terminal domains carry putative nu- Salmonella Typhimurium SPI-6-encoded T6SS gene cluster.…”
mentioning
confidence: 99%
“…clease activities (42)(43)(44)(45). The upstream operon (STM0266-STM0271) consists of a number of genes encoding machine subunits and two genes of unknown function.…”
mentioning
confidence: 99%